Profil ekspresi von Hippel-Lindau (pVHL) pada adenokarsinoma duktal pankreas dan jaringan pankreas non-neoplastik serta hubungannya dengan faktor klinikopatologi - Jessica Prisscila; Marini Stephanie; Nur Rahadiani; Amelia Fossetta Manatar; Ening Krisnuhoni (Majalah Patologi Indonesia, 2026)
Introduction Pancreatic malignancy, primarily Pancreatic Ductal Adenocarcinoma (PDAC), presents a significant challenge due to its aggressive nature and late-stage diagnosis. This study explores the role of von Hippel-Lindau gene product (pVHL) in PDAC and non-neoplastic pancreatic tissues, investigating their relationship with PDAC clinicopathological characteristics. Method This research was carried out at the Faculty of Medicine Universitas Indonesia/Dr. Cipto Mangunkusumo General Hospital.   The cases analyzed spanned from January 2012 to September 2023. Immunohistochemistry of pVHL was used, and the Histoscore/H-score calculations were utilized to classify pVHL expression as either high or low. Results A total of 54 cases of PDAC and non-neoplastic pancreatic tissue exhibited varying levels of pVHL expression. Cases of PDAC with positive surgical margin, absence of lymphovascular and perineural invasion, pT2, pN0, M0 stage, and survival exceeding 7 months were the profiles in which low pVHL expression was detected. Significant result was found on the correlation between pVHL with pN status. Conclusion The levels of pVHL expression varied between PDAC and non-neoplastic pancreatic tissue. There were no differences in the clinicopathological profile of PDAC tumors, except for pN stage. Further research, with a larger sample size, is needed to determine pVHL's diagnostic value and its expression in different clinicopathological profiles.